2019
DOI: 10.1108/ilt-05-2018-0170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the friction and wear effects of graphene nanoparticles in oil on the ring/cylinder liner of internal combustion engine

Abstract: Purpose This study aims to investigate the tribological characteristics of a Napier-type second piston ring against a cylinder liner in the presence of graphene nano-additives mixed into 5W40 fully synthetic engine oil. Design/methodology/approach Wear tests were carried out in the boundary lubrication condition using a reciprocating tribometer, and real engine tests were performed using a single spark ignition Honda GX 270 test engine for a duration of 75 h. Findings The experimental results of the tribom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Among the samples, sample rGO6 (0.02 wt %) presented superior tribological properties by exhibiting the lowest COF value. It is evident that additional protection to rubbing surfaces from wear was provided, due to the formation of a protective layer, represented by colorful regions, as displayed below in the optical microscopy images ( Figure 5 ) [ 40 ]. The sample rGO7 exhibited higher COF than rGO4, rGO5 and rGO6, although its rGO concentration was lower.…”
Section: Resultsmentioning
confidence: 99%
“…Among the samples, sample rGO6 (0.02 wt %) presented superior tribological properties by exhibiting the lowest COF value. It is evident that additional protection to rubbing surfaces from wear was provided, due to the formation of a protective layer, represented by colorful regions, as displayed below in the optical microscopy images ( Figure 5 ) [ 40 ]. The sample rGO7 exhibited higher COF than rGO4, rGO5 and rGO6, although its rGO concentration was lower.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent thermal [13] and mechanical properties of graphene, along with its unique two-dimensional structure, enable further friction and wear reduction by the bio-lubricant. Demirtas and Kaleli [14] tested the performance of graphene in actual piston ring-cylinder liner working condition and found that the graphene was readily able form a protective layer, hence increasing the tribological performance. Zulkifli and Azman [15] have found that graphene can improve the tribological properties of palm-based Trimethylolpropane (TMP) ester blended with Polyalphaolefin (PAO).…”
Section: Introductionmentioning
confidence: 99%
“…As new type lubricating materials, two-dimensional materials such as graphene, hexagonal BN and MoS 2 have received widespread attention because of their unique physical and chemical properties (Rosenkranz et al , 2020; Zhang et al , 2019). In particular, graphene has received significant attention (Penkov et al , 2014; Berman et al , 2014; Fan et al , 2014; Demirtas et al , 2019). Dispersants or organic modification of graphene is usually used to improve its dispersion stability in oil-based lubricants (Zhang et al , 2011; Yang et al , 2017; Lin et al , 2011).…”
Section: Introductionmentioning
confidence: 99%